Features of anesthesiological management for transnasal surgical in pituitary adenomas: literature review - Lesia Y. Pechera; Mykola O. Guk; Arthur O. Mumliev (Ukrainian Neurosurgical Journal, 2017)
Tumors of the pituitary gland make up about 10% of all neoplasms of the brain, mainly represented by adenomas. A feature of a larger number of adenomas is the symptoms of hypersecretion of the pituitary hormones, which leads to typical changes in the patient’s body. Surgical removal of pituitary tumors is performed through endoscopical transnasal access. Understanding the individualities of patients, the disease course and the operation course helps the anesthesiologist to ensure adequate preoperative preparation, anesthesia and postoperative management for patients, which reduces the number of complications and facilitates the early recovery of patients.